ANALISIS PELAKSANAAN KEGIATAN BERWIRAUSAHA DI MASA PANDEMI COVID-19 (Studi Kasus Pada Mahasiswa Prodi PAP Angkatan Tahun 2017) - Ilyas Dhaputri Nur Hajizah; Cicilia Dyah Sulistyaningrum Indrawati; Tri Murwaningsih (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
The Covid-19 pandemic has had a huge impact on the economy, especially in the field of entrepreneurship. The implementation of online learning among students provides free time for entrepreneurship, but not all students have the will to become entrepreneurs. The aims of this study was to find out the implementation of entrepreneurial activities in students, the supporting and inhibiting factors, and how to overcome the problem. The approach of this study was qualitative descriptive method, and single fixed strategy. Sources of data used are informants, locations, and analysis documents. The sample method of this study were the purposive sampling and snowball sampling. The validity of the data used data triangulation and method triangulation, while the data analysis technique used is an interactive model analysis technique, with stages, data collection, data reduction, data presentation, and drew conclusions. The results showed (1) the implementation of student entrepreneurship during the pandemic included strengthening motivation, goals, capital, management, business ideas, product types, marketing, and administration (2) factors that supported included willingness, free time, income, hobbies, conditions that support, competition, support from the environment. The inhibiting factors included difficulty in interacting with customers, difficulty in managing time, customer debt, and shipping costs (3) effort to overcome obtacles were to comply with health protocols,to perform time management, to reduce customer debt, to provide promos and discounts, to consistently carried out, and evaluated.